THE USE OF STORY FACE IN TEACHING READING COMPREHENSION OF NARRATIVE TEXT IN SMK SWASTA DWIWARNA MEDAN - Maisaroh Sartika Damanik; Rika Rika; Yeni Erlita (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
THE USE OF STORY FACE IN TEACHING READINGCOMPREHENSION OF NARRATIVE TEXT IN SMK SWASTADWIWARNA MEDAN*Maisaroh sartika Damanik**Rika**Yeni ErlitaABSTRACTThis study was aimed to find out the process of teaching reading comprehensionthrough story face of narrative text and students’ problems in the process oflearning reading comprehension through story face of narrative text. The researchwas conducted by using descriptive qualitative. The data were analyzed byqualitative analysis technique which consists of three procedures, namely: datacondentation, data display and drawing/conclusion. The data were the result ofobserving and interviewing of students at SMK Swasta Dwiwarna Medan. Thedata were analyzed based on teaching reading comprehension through story faceby Randolp (2012). The findings showed that the process of teaching learningreading by using story face could help the students in learning reading butteaching reading comprehension by using story face was still less effective ingrade tenth in SMK Swasta Dwiwarna Medan. The teacher had followed theprocedure well based on the Randolp(2012), but the teacher did not manage thetime well. There were some students’ problems in learning readingcomprehension of narrative text by using story face. The problems were: (a)students lack vocabulary mastery, (b) The students had problem to decode wordsand sentence, (c) Students had problem to get main idea of the text and to figureout the inference of the text, (d) Students had habit of slow reading, (e) Studentshad problem in working memory to remember the text, (f) students were beingpassive during learning process and they did not confidence, they felt afraid tomake a mistake in learning reading.Key words:Reading comprehension, students’ problems in learning reading,Story Face, Teaching reading story face.